Evaluation of Rice Bran Extract as a Nitrogen Source for Improved Hemicellulosic Ethanol Production from Sugarcane Bagasse by New Xylose-Fermenting Yeast Strains Isolated from Brazilian Forests - Martiniano, Sabrina E.; Philippini, Rafael R.; Chandel, Anuj K.; Rosa, Carlos A.; Pagnocca, Fernando C. [UNESP]; da Silva, Sílvio S. (Springer Nature, 2013)
Xylose is the main sugar in hemicellulosic hydrolysates and its fermentation into ethanol by microorganisms is influenced by nutritional factors, such as nitrogen source, vitamins and other elements. Rice bran extract (RBE) is an inexpensive nitrogen source primarily consisting of high amount of protein. This study evaluates the potential of RBE as a nitrogen source for the hemicellulosic ethanol production from sugarcane bagasse dilute acid hydrolysate by novel yeast strains Scheffersomyces shehatae (syn. Candida shehatae) CG8-8BY and Spathaspora arborariae UFMG-HM19.1A, isolated from Brazilian forests. Two different media formulations were used for inoculum preparation and production medium, using yeast extract and RBE as nitrogen sources. S. shehatae CG8-8BY showed ethanol production of 17.0 g/l with the ethanol yield (0.33 g/g) and fermentation efficiency (64 %) from medium supplemented with RBE. On the other hand, S. arborariae presented 5.4 g/l of ethanol production with ethanol yield (0.14 g/g) and fermentation efficiency (21 %) in a fermentation medium supplemented with RBE. Appropriate media formulation is an important parameter to increase the productivity of bioconversion process and RBE proved to be an efficient and inexpensive nitrogen source to supplement sugarcane bagasse hemicellulosic hydrolysate for second generation ethanol production. © 2013 Society for Sugar Research & Promotion.
Keywords: Nitrogen source; Rice bran extract; Scheffersomyces shehatae; Second generation ethanol; Spathaspora arborariae; Sugarcane bagasse